2013
DOI: 10.1148/radiol.13122567
|View full text |Cite
|
Sign up to set email alerts
|

Digital Compared with Screen-Film Mammography: Performance Measures in Concurrent Cohorts within an Organized Breast Screening Program

Abstract: Although DR is equivalent to SFM for breast screening among women aged 50-74 years, the cancer detection rate was lower for CR. Screening programs should monitor the performance of CR separately and may consider informing women of the potentially lower cancer detection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 33 publications
5
54
2
2
Order By: Relevance
“…Chiarelli et al found that overall cancer detection rates were lower with CR (3.4 per 1000 women screened) compared to film (4.8 per 1000) or DR (4.9 per 1000) with CR significantly less likely to help detect invasive cancers. 26 Although a similar trend in overall cancer detection rates was reported by Seradour et al (CR: 5.5 per 1,000, film: 6.6 per 1000 and DR: 7.1 per 1000), there was no significant difference in invasive cancer detection. 16 Investigations in Australia also showed no significant difference in invasive and small invasive cancer detection rates between CR and DR; these studies also concluded that CR was at least as good as film, based on overall cancer detection rates.…”
Section: Comparison Of Digital Mammography Detectorssupporting
confidence: 73%
See 2 more Smart Citations
“…Chiarelli et al found that overall cancer detection rates were lower with CR (3.4 per 1000 women screened) compared to film (4.8 per 1000) or DR (4.9 per 1000) with CR significantly less likely to help detect invasive cancers. 26 Although a similar trend in overall cancer detection rates was reported by Seradour et al (CR: 5.5 per 1,000, film: 6.6 per 1000 and DR: 7.1 per 1000), there was no significant difference in invasive cancer detection. 16 Investigations in Australia also showed no significant difference in invasive and small invasive cancer detection rates between CR and DR; these studies also concluded that CR was at least as good as film, based on overall cancer detection rates.…”
Section: Comparison Of Digital Mammography Detectorssupporting
confidence: 73%
“…21,22 The only common finding between all studies was that DR was significantly better at detecting ductal carcinoma in situ (DCIS). 16,21,22,26 All of these studies 16,21,22,26 examined concurrent cohorts of a screening population (aged 50e74) and all mammograms were double-read, except for those in the study by Chiarelli et al 26 which were single-read; however, this would have been the case for film, CR and DR images. Differences in the study results may be due to differences in the CR systems and it would be interesting to see not just a comparison of CR and DR, but a comparison by system manufacturer.…”
Section: Comparison Of Digital Mammography Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recently published study comparing the performance of film mammography with that of DR and CR digital mammography in the OBSP, 11 we found that the cancer detection rate for DR was 4.9 per 1000 with 95% confidence interval (CI) of 4.7−5.2 while that for CR was 3.4 per 1000 with 95% CI: 3.0−3.9. These confidence intervals are well separated, indicating that the 30.6% difference is statistically significant.…”
Section: A Clinical Performancementioning
confidence: 89%
“…Comparisons of cancer detection rates have either shown that CR is comparable to screen-film overall [30,31], or comparable for invasive cancer only [26], or, worryingly, inferior to screen-film [32]. The difference in results between these studies is, in my view, attributed to differences in the CR performance of different vendors.…”
Section: Advances In Technologymentioning
confidence: 96%